Synthesis and properties of the materials obtained by SHS mode for radiation protection; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Isachenko D. S. Dmitry Sergeevich; Dolmatov O. Yu. Oleg Yurevich; Semenov A. O. Andrey Olegovich; Chursin S. S. Stanislav Sergeevich; Kuznetsov M. S. Mikhail Sergeyevich (2016, 2016)
Title screen